Scattering of Sodar Signal by Turbulence in Homogenous, Isotopic and other Mediums - Babu, M. Hareesh; Raju, D.S.S.N; Sarvani, A; Rao, M. Purnachandra (International Journal of Computer Sciences and Engineering, 2014)
Turbulence is very difficult to define succinctly except by its contrast with laminar flow and there is no universally accepted model to describe quantitatively the details of medium. If it is difficult to understand about turbulence then itï¿½s also difficult to understand scattering of sound, i.e., sodar signal by turbulence. For the purpose of this analytical study, it is assumed that turbulence in the lower atmosphere with some considerations and developed mathematical algorithms and observed different plots to estimate the scope of the sound scattering in homogenous, isotopic and other mediums. All these mathematical algorithms and plots has developed in the scientific software MATLAB. These results are compared with the early studies and concludes that past and present studies found similar predictions for the scattering of sodar signal by turbulence.